FRAILTY AND MORTALITY ASSOCIATION IN PATIENTS WITH COVID-19 : A SYSTEMATIC REVIEW - Frida Setiawan, Yenny (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
When a person's physiological reserve is low, they are more susceptible to the negative effects of stress, which can lead to poor health outcomes. This condition is known as frailty. This condition is linked to a number of chronic conditions, many of which are risk factors for the outcomes of SARS-COV-2 infections in elderly patients. This review aims to describe frailty as a physiological vulnerability agent during the Covid-19 pandemic in elderly patients. It will do so by providing a summary of the direct and indirect effects caused by the SARS-COV-2 infection, as well as its prognosis in frail individuals, as well as the interventions and recommendations that can be used to reduce the effects of these infections. However, other scales have also associated frailty with longer hospital stays and more severe forms of the disease. Cohort studies have shown that patients with a Clinical Frailty Scale that is higher than five have a higher risk of mortality and use of mechanical ventilation after Covid-19. In addition, the pandemic's indirect effects have a negative impact on the health status of people who are older in age. As a result of the aforementioned, a holistic intervention is proposed. This intervention is based on a comprehensive geriatric assessment for frail patients and places an emphasis on physical activity and nutritional recommendations. If successful, this intervention could serve as a potential preventive intervention in viral infections caused by Covid-19. One of the primary contributors to a precarious state of life as a result of the gradual loss of physiological functions and a key factor in the development of pathological aging is simply getting older. In this particular study, the overall mortality rate for patients was found to be 38.3% on average.